Increase of the Serum FGF-23 in Ossification of the Posterior Longitudinal Ligament. Issue 5 (August 2019) - Kawaguchi, Yoshiharu; Kitajima, Isao; Nakano, Masato; Yasuda, Taketoshi; Seki, Shoji; Suzuki, Kayo; Yahara, Yasuhito; Makino, Hiroto; Ujihara, Yasuhiro; Ueno, Tomohiro; Kimura, Tomoatsu
Study Design: Case-control study. Objectives: To determine the possible pathogenesis of ossification of the posterior longitudinal ligament (OPLL) in regard to the serum concentration of fibroblast growth factor 23 (FGF-23). Methods: The study included 95 patients with OPLL and a control group of 73 age- and sex-matched volunteers. The serum concentrations of FGF-23, creatinine (Cre), alkaline phosphatase, calcium (Ca), inorganic phosphate (Pi), and hypersensitive C-reactive protein (hs-CRP) were analyzed from blood samples, and Cre, Ca, Pi, and tubular reabsorption of phosphate were measured using urine samples. We evaluated the severity of ossified spinal lesions in patients with OPLL according to the ossification index (the OP index and the OS index). Data was compared between the OPLL and control group and between the OPLL progression and no progression group. Results: Serum FGF-23 and hs-CRP were higher, and serum Pi was lower in patients with OPLL than in the controls. There was a positive correlation between FGF-23 and hs-CRP and a negative correlation between serum Pi and the OS index; however, the correlations were very weak. Overall, 31.7% of patients had progression of OPLL during follow-up. FGF-23 and hs-CRP were higher in the progression group than in the no progression group. Conclusions: These results might indicate that FGF-23 and hs-CRP are positive markers for OPLL. Phosphate metabolism via FGF-23 might be a target for future study on the pathogenesis of OPLL.